Principal's Influence On Organizational Leadership Management Smp Negeri 4 Banguntapan - Maya Syharani Adisti Bana; Zahra Syifarani; Defrian Rizki Muncar Atmana (Insight School Academy, 2023)
Introduction to The Problem: Leadership strongly influences an organization or agency; leadership style also has the potential for future performance. Good leadership will also have a good impact on the organization. Purpose: This is where you explain ‘why’ you undertook this study. If you are presenting new or novel research, explain the problem that you have solved. If you are building upon previous research, briefly explain why you felt it was essential to do so. This is your opportunity to let readers know why you chose to study this topic or problem and its relevance. Let them know what your crucial argument or main finding is. Design/methods/approach: The method or method used in this observation is a qualitative method system. The qualitative method collects data through observation, observation, and interviews of a school with various reports related to the problem to be solved. Findings: Here, you can explain ‘what’ you found during your study, whether it answers the problem you set out to explore, and whether your hypothesis was confirmed. You must be clear and direct and give exact figures rather than generalize. It is important not to exaggerate or create an expectation that your paper will not fulfill. Research implications/limitations: Here, you can explain characteristics of design or methodology that impacted or influenced the interpretation of the findings from your research. They are the constraints on generalizability, applications to practice, and utility of findings that result from how you initially chose to design the study or the method used to establish internal and external validity of the result of unanticipated challenges that emerged during the study. Your research may have multiple limitations, but you must discuss only those directly related to your research problems. Originality/value: This is your opportunity to provide readers with an analysis of the value of your results. It is a good idea to ask colleagues whether your analysis is balanced and fair, and again, it is essential not to exaggerate. You can also conjecture what future research steps could be.